Alternative Communication: A Tool for Social Inclusion of People with Disabilities - Deliyore-Vega, María del Rocío (2018)
In a mainly oral society, those who use alternative forms of communication tend to be marginalized, and this limits equal opportunities. Therefore, this article is based on qualitative documentary research in which the problem posed determines how access to alternative and augmentative communication affects the social inclusion of people with disabilities. The objective is to determine the relationship existing between the theoretical assumptions about inclusive processes and their connection with alternative communication. To achieve this objective, the paper offers a compilation of updated sources on the subject the main researchers in the field have proposed. Subsequently, the contents involved are related using a conceptual scheme. Finally, an analysis of the data is carried out to achieve the proposed research objective. As a result, it was found that both national and international legislation, as well as research and pedagogical currents, promote equal opportunities and the inclusion of the population with disabilities. In spite of this situation, even people with communication barriers still do not have adequate access to dialogue. Results show that alternative communication is an indispensable right for a process of learning; however, students with communication barriers still attend classes without resources allowing their participation. It is also shown that there can be no learning without communication. Thus, the population with communication barriers that attend the classes without an assisted resource sees not only its right to expression violated, but also their right to education.